Penggunaan Kecerdasan Buatan Dalam Mengurangi Perilaku Penghindaran Iklan - Siratan, Elkuny Dovir; Yulita, Henilia; Widaningsih, Titi (Innovative: Journal Of Social Science Research, 2024)
Advertisement has become one of the factors used to create influence on consumer purchasing decisions.Massive exposure to advertisements causes the emergence of advertisement avoidance behavior.This study aims to analyze the use of artificial intelligence in reducing advertisement avoidance behavior.Advertisement avoidance behavior includes cognitive, affective, and conative advertisement avoidance.The method used is a systematic literature review (SLR) to collect and critically analyze by presenting data and findings from various previous studies.The results of this study conclude that the use of personalized AI can reduce advertisement avoidance behavior.